2018
DOI: 10.5755/j01.eis.0.12.21875
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Development of the Corporate Bond Market in Latvia

Abstract: regression analysis. In the result of the analysis, the determinants of the corporate bond market development in Latvia were analysed, where 27 factors as detected by the theoretical analysis to be influencing the corporate bond market development in a country were applied to Latvia. The regression analysis has demonstrated the influence of GDP per capita, amount of domestic savings, real GDP growth, amount of government bonds as the share of GDP and regulatory quality on the amount of the corporate bonds outs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As part of the quantitative analysis, this study employs a fixed effects panel regression model to analyse bond market development from a country-level perspective, adapting the methodology from Smaoui et al (2017), Mu et al (2013), andTocelovska et al (2018). This approach accounts for unobserved country-specific factors, is more robust to omitted variable bias than pooled ordinary least squares, and is less restrictive than the random effects model.…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of the quantitative analysis, this study employs a fixed effects panel regression model to analyse bond market development from a country-level perspective, adapting the methodology from Smaoui et al (2017), Mu et al (2013), andTocelovska et al (2018). This approach accounts for unobserved country-specific factors, is more robust to omitted variable bias than pooled ordinary least squares, and is less restrictive than the random effects model.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Smaoui et al (2017) examined a sample of 22 developing countries and found economic size (GDP expressed in purchasing-power-parity), trade openness (exports to GDP), investment profile (risk rating derived from a combination of contract expropriation, profits repatriation, and payment delays), bureaucratic quality (estimate of bureaucratic autonomy from political pressure and its conservatism), banking concentration (sum of largest three banks' assets measured against the total assets in the supervision of commercial banks), and lastly the foreign exchange rate volatility (standard deviation of the nominal exchange rate logarithm difference) to be important. Tocelovska et al (2018) analysed 31 country-sample revealing GDP per capita, amount of domestic savings, real GDP growth, amount of government bonds as the share of GDP and regulatory quality on the amount of outstanding corporate bonds. Mu et al (2013) studied 24 corporate bond markets and identified that economic size, GDP per capita, and land area variables were significant.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation